(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The present study was designed to analyze the effect of remedial yoga and physical fitness regimen training on selected physiological and psychological variables among obese college men. Remedial yoga and physical fitness training selected as independent variables for this study. To achieve the purpose of the study, 60 obese college men studying in the M.A.M. College of Engineering and Technology, Tiruchirappalli. The age of the subjects ranged from 18 to 21 years. The selected subjects were randomly assigned to two experimental groups and one control group of twenty (n=20) each for experimental group. Experiment Group I (RGC I), Experiment Group II (FRG) and control group (Group III). Group I underwent Remedial Yoga practices, Group II underwent Fitness Regimen Training for duration of 12 weeks. The control group (Group III) was asked to refrain from any special training except their regular practice and playing schedule. All the subjects of three groups were tested on selected physical and physiological variables before and after the treatment. The analysis of covariance (one-way ANCOVA). Whenever the ‘F’ ratio for adjusted test was found to be significant, the Scheffe’s test was applied as post-hoc test to find out paired mean difference. In all the cases 0.05 level was fixed as significant level. The results were drawn accordingly.